Padronização e validação de uma metodologia para detecção de polimorfismos associados ao processo de resistência aos benzimidazóis em Trichuris trichiura - Valéria Nayara Gomes Mendes de Oliveira (2020)
Human geo-helminthiasis can be caused, mainly, by four species of gastrointestinal nematodes, Ascaris lumbricoides, Trichuris trichiura, Necator americanus and Ancylostoma duodenale. Preventive chemotherapy is recommended by World Health Organization as the main strategy to control infections caused by nematodes in humans and aims to eliminate the morbidity associated with these infections. Such a strategy consists of the periodic administration of anthelmintics. The drugs albendazole and mebendazole are the most commonly used due to their broad spectrum of activity, low cost and ease of administration. Although these drugs are effective, decreasing the intensity of infections, they have the potential to exert a selection pressure that can result in the establishment of resistance. Among nematodes of veterinary importance there is evidence that the constant use of benzimidazoles has selected populations of resistant parasites. There is evidence in the literature of resistance to these drugs in nematodes that infect humans, mainly for the species T. trichiura. The occurrence of Single Nucleotide Polymorphism (SNP) within three specific codons, 167, 198 and 200 of the β-tubulin gene, are associated with the mechanism of resistance to benzimidazoles in nematodes. Therefore, the objective of this work was to standardize and validate a methodology for the detection of polymorphisms associated with the process of resistance to benzimidazoles in T. trichiura. Non-mutated and mutated controls were constructed using conventional PCR and site-directed mutagenesis, respectively. The ARMS-PCR methodology was successfully established to evaluate codons 167, 198 and 200 of the β-tubulin gene. Initially, 462 samples were analyzed from individual eggs obtained from 37 patients from five Brazilian states. The codon 198 mutation was observed at a frequency of 4.8% (20/462), while for the other two codons no polymorphism was observed. A total of 20 samples were submitted to sequencing for validation of the standardized technique. It is concluded that there is a moderate frequency of mutation in codon 198 of the β-tubulin gene in the population of T. trichiura analyzed. This is the first report of the presence of this mutation in populations of this species in Brazil, this fact and the already observed emergence of the problem in other species reinforces the need for regular monitoring of SNPs related to benzimidazole resistance with techniques that are highly sensitive and specific.